2014
DOI: 10.3747/pdi.2012.00331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biocompatible Peritoneal Dialysis Solution on Residual Renal Function: A Systematic Review of Randomized Controlled Trials

Abstract: ♦ Introduction: Residual renal function (RRF) plays an important role in outcome of peritoneal dialysis (PD) including mortality. It is, therefore, important to provide a strategy for the preservation of RRF. The objective of this study was to evaluate relative protective effects of new glucose-based multicompartmental PD solution (PDS), which is well known to be more biocompatible than glucosebased conventional PDS, on RRF compared to conventional PDS by performing a systematic review (SR) of randomized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 46 publications
4
21
0
2
Order By: Relevance
“…Our meta-analysis differed from the analysis by Seo et al (25) in that we included two trials (studies by Fernández-Perpén et al [14] and Weiss et al [22]) not in their analysis. Also, we excluded two trials that the analysis by Seo et al (25) included; we excluded the study by Fan et al (27) for the reasons explained above, and also, we excluded the study by Williams et al (28) It is unclear why the use of neutral-pH, low-GDP solutions would result in improved RRF. Some have postulated that the reduced GDP content and the resultant lower levels of AGEs could prevent damage to the kidneys and thus, preserve RRF (4).…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…Our meta-analysis differed from the analysis by Seo et al (25) in that we included two trials (studies by Fernández-Perpén et al [14] and Weiss et al [22]) not in their analysis. Also, we excluded two trials that the analysis by Seo et al (25) included; we excluded the study by Fan et al (27) for the reasons explained above, and also, we excluded the study by Williams et al (28) It is unclear why the use of neutral-pH, low-GDP solutions would result in improved RRF. Some have postulated that the reduced GDP content and the resultant lower levels of AGEs could prevent damage to the kidneys and thus, preserve RRF (4).…”
Section: Discussionmentioning
confidence: 39%
“…There have been two published meta-analyses comparing neutral-pH, low-GDP and conventional solutions by Cho et al (23,24) and Seo et al (25). Both have suggested that prolonged treatment (i.e., .12 months) with neutralpH, low-GDP solutions resulted in improved RRF.…”
Section: Discussionmentioning
confidence: 99%
“…This patient was maintained on ramipril and bumetanide throughout most of her clinical course. A meta-analysis of existing clinical trials provides evidence that the use of more biocompatible dialysate fluids is associated with better preservation of RRF, although the mechanism is not clear (5). Given that patients who are highly comorbid have a more rapid rate of decline of RRF, this may strengthen the argument to use such fluids, at least for this group.…”
Section: Rrfmentioning
confidence: 86%
“…In the balANZ trial, the slope of the decline in RRF was not significantly different between the low-GDP and the conventional group, but the time to anuria was longer in the group treated with low-GDP solutions (17). In a subsequent meta-analysis, RRF and urine volume 12 months after the start of PD were significantly higher in patients treated with low-GDP as compared to conventional solutions (21,22). Whereas the beneficial effect of low-GDP solutions on peritoneal membrane function has strong theoretical underpinnings, the effects on RRF and/or diuresis are more enigmatic, although it has been proposed that the…”
Section: Is the Effect Of Low-gdp Solutions On Residual Renal Functiomentioning
confidence: 99%